2010
DOI: 10.3411/col.08230102
|View full text |Cite
|
Sign up to set email alerts
|

Gaining Ground: Wetlands, Hurricanes and the Economy; The Value of Restoring the Mississippi River Delta

Abstract: The Authors David Batker, cofounder and executive director of Earth Economics, has worked for 20 years in over 30 countries changing economic policy to effect measurable physical improvements for people and ecosystems. His areas of work include climate change, fisheries, forest, coastal management, hazardous waste, land use, energy, agriculture, trade and international finance and improving lending requirements of international banks. With a B.S. in geology and biology from Pacific Lutheran University, he comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
58
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(59 citation statements)
references
References 95 publications
1
58
0
Order By: Relevance
“…Bucher and Huszar (1995) concluded that the environmental costs of the project may exceed the benefits, and would negatively impact on biodiversity and the regulation of downstream flows. In the Gulf of Mexico, Batker et al (2010) reported, in a recent review, that the Mississippi River Delta ecosystems provide at least US$ 12-47 billion in annual benefits, and that such vast natural assets provide a basis for national employment and economic productivity.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Bucher and Huszar (1995) concluded that the environmental costs of the project may exceed the benefits, and would negatively impact on biodiversity and the regulation of downstream flows. In the Gulf of Mexico, Batker et al (2010) reported, in a recent review, that the Mississippi River Delta ecosystems provide at least US$ 12-47 billion in annual benefits, and that such vast natural assets provide a basis for national employment and economic productivity.…”
Section: Introductionmentioning
confidence: 99%
“…Coastal wetlands and dunes provide vital protection against storms and hurricanes by wave attenuation and water velocity reduction. Batker et al (2010) discuss the flood protection value of brackish and freshwater wetlands in the Mississippi Delta, and consider it unique in the provision of flood protection in North America, in both water quantity and the vastness of area served.…”
Section: Introductionmentioning
confidence: 99%
“…Ecosystem degradation in the form of wetland loss, partly as a result of oil and gas industry infrastructure, has increased the risk of natural disasters to coastal communities [56]. Batker et al [57] carried out a partial assessment of the value of ecosystem services of the Mississippi River delta. They reported an annual value of ecosystem services of $12 to $47 billion and a minimum natural capital asset value of the delta of $330 billion to $1.3 trillion.…”
Section: Discussionmentioning
confidence: 99%
“…The wetlands, estuaries, and barrier islands making up the delta provide great economic value, serving as nursery grounds for both sport and commercial fisheries, providing wildlife habitat, attenuating storm effects, supporting the largest port by tonnage in the world, and containing energy reserves. With the loss of coastal wetlands comes a diminishment in the ecosystem services provided (Batker et al, 2010;Batker et al, 2014).…”
Section: Introductionmentioning
confidence: 99%